2022
DOI: 10.4049/jimmunol.2100643
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Expressing an HLA-DR1 Chimeric Antigen Receptor Target Autoimmune CD4+ T Cells in an Antigen-Specific Manner and Inhibit the Development of Autoimmune Arthritis

Abstract: Ag-specific immunotherapy is a long-term goal for the treatment of autoimmune diseases; however developing a means of therapeutically targeting autoimmune T cells in an Ag-specific manner has been difficult. Through the engineering of an HLA-DR1 chimeric Ag receptor (CAR), we have produced CD8+ CAR T cells that target CD4+ T cells in an Ag-specific manner and tested their ability to inhibit the development of autoimmune arthritis in a mouse model. The DR1 CAR molecule was engineered to contain CD3ζ activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Our data are consistent with recent reports regarding the potential for antigen-specific T cell depletion therapy for autoimmunity. For example, in a partially humanized murine model of rheumatoid arthritis, pMHCII-CAR T cells composed of HLA-DR1 bound to a type II collagen peptide were effective at preventing collagen-induced arthritis ( 35 ). The pMHCII-CAR approach represents an alternative to a recent report using a MHCII-TCR fusion (5M)CAR to prevent autoimmune diabetes ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with recent reports regarding the potential for antigen-specific T cell depletion therapy for autoimmunity. For example, in a partially humanized murine model of rheumatoid arthritis, pMHCII-CAR T cells composed of HLA-DR1 bound to a type II collagen peptide were effective at preventing collagen-induced arthritis ( 35 ). The pMHCII-CAR approach represents an alternative to a recent report using a MHCII-TCR fusion (5M)CAR to prevent autoimmune diabetes ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Whittington et al reported recently that DR1-CII CAR-T cells can specifically and effectively recognize and kill CD4 + T cells which are specific for the CII autoantigen in vivo in CIA mice. This leads to reduced autoantibody production, decreased collagen II-specific CD4 + T cell response and diminished severity of autoimmune arthritis in mice [175]. Furthermore, HLA-A*02 CAR-Treg cells were generated and have shown to be highly effective in preventing immune responses mediated by HLA-A*02 in both, human and mice [176].…”
Section: Antigen-specificity Of Treg Cells and Use Of Chimeric Antige...mentioning
confidence: 99%
“…The half-life time of CAR-T cells was reported to be relatively short after passive transfer into CIA mice and it was not possible to detect CAR-T cells in mice later than day 10 after adoptive cell transfer [175]. However, CAR-CD8 + Treg cells are still functional and can activate T cells in vivo for at least 80 days [181].…”
Section: Antigen-specificity Of Treg Cells and Use Of Chimeric Antige...mentioning
confidence: 99%
“…Furthermore, they demonstrated that TNP CAR Tregs preferentially migrated to TNP-sensitized colon and prevented the development of colitis in wild-type mice. Since then, Tregs have been engineered with CAR technology as potential therapy for several other autoimmune diseases and allergy-related diseases, such as experimental autoimmune encephalomyelitis (EAE) (46,47), type I diabetes (48), asthma (49), hemophilia A (50, 51), vitiligo (52), and arthritis (53). Additionally, several papers describe the protection of CAR Tregs from the development of GVHD after stem cell transplantation in murine models (54)(55)(56).…”
Section: Car T-cells and Car-treg Cellsmentioning
confidence: 99%